Edukasi Terapi Tertawa sebagai Intervensi Non-Farmakologi untuk Mengatasi Perilaku Kekerasan pada ODGJ di Yayasan Mitra Mulia Husada Palembang - Raden Surahmat; Mareta Akhriansyah; Nuriza Agustina; Aris Citra Wisuda; Putinah Putinah; Muhamad Andika Sasmita Saputra; Sulardi Sulardi (Jurnal Abdimas Kesehatan (JAK), 2026)
Violent behavior is currently a complex psychosocial and neurobiological problem as well as an emergency health problem, both in the form of physical and psychological violence in real interactions and media. This condition can be detrimental to oneself, others and the environment so that real solutions are needed through non-pharmacological efforts, namely laughter therapy. This activity aims to provide education to ODGJ about to reduce stress, improve emotional control, and help patients become calmer and more cooperative. This activity was carried out for 36 people at the Mitra Mulia Husada Palembang Foundation on February 08-09, 2025, using s, SOPs for and observation sheets. The results of the evaluation of this activity showed that there was an increase in understanding and patients at risk of violent behavior were able to undergo laughter therapy. The results of observations showed that participants appeared calmer, more cooperative and appeared happy. These results prove that laughter can naturally help to stabilize emotions, reduce stress hormone levels, create feelings of calm, comfort, happiness and help them build the ability to control emotional reactions better. It is recommended that the management of the Mitra Mulia Husada Palembang Foundation implement as an alternative intervention for ODGJ to overcome violent behavior.